2008
DOI: 10.4049/jimmunol.181.1.690
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B Is Involved in the Trafficking of TNF-α-Containing Vesicles to the Plasma Membrane in Macrophages

Abstract: TNF-α is a potent proinflammatory cytokine, essential for initiating innate immune responses against invading microbes and a key mediator involved in the pathogenesis of acute and chronic inflammatory diseases. To identify molecules involved in the production of TNF-α, we used a functional gene identification method using retroviral integration-mediated mutagenesis, followed by LPS-stimulated TNF-α production analysis in macrophages. We found that cathepsin B, a lysosomal cysteine proteinase, was required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 45 publications
(44 reference statements)
8
79
0
3
Order By: Relevance
“…Nonlysosomal cathepsin B has been implicated in both pathological and physiological processes. In cells of the monocyte/macrophage lineage, cytosolic cathepsin B was suggested to regulate secretion of tumor necrosis factor-␣ induced by inflammatory stimuli (55). Further, multiple reports have implicated nonlysosomal cathepsin B in promoting myoblast fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Nonlysosomal cathepsin B has been implicated in both pathological and physiological processes. In cells of the monocyte/macrophage lineage, cytosolic cathepsin B was suggested to regulate secretion of tumor necrosis factor-␣ induced by inflammatory stimuli (55). Further, multiple reports have implicated nonlysosomal cathepsin B in promoting myoblast fusion.…”
Section: Discussionmentioning
confidence: 99%
“…It's known that the activation of NLRP3 infl ammasome by a variety of stimuli depends on lysosomal rupture, K + effl ux and/ or production of reactive oxygen species (ROS) (Ha et al, 2008;Tschopp and Schroder, 2010). To further explore the mechanism underlying IL-1β induction by T. schoenleinii, we fi rst utilized CA-074 Me to inhibit activity of Cathepsin B, which is usually produced due to lysosomal rupture.…”
Section: T Schoenleinii Triggers Il-1β Production From Human Monocytesmentioning
confidence: 99%
“…A recent study identified an additional requirement for cathepsin B, at least for a proportion of TNF-a release in some macrophages. Ablation of cathepsin B led to accumulation of the membrane bound TNF-a pro-form in intracellular vesicles implying a possible role for cathepsin B in fusion of these vesicles with the plasma membrane [50]. The relevant substrates for cathepsin B were not identified; therefore, it remains to be established whether cathepsin B is acting within the endosome/lysosome compartment or within the cytosol.…”
Section: Reciprocal Relationships Between Cytokines and Lysosomal Catmentioning
confidence: 99%